1977
DOI: 10.1080/00071667708416402
|View full text |Cite
|
Sign up to set email alerts
|

Plasma growth hormone concentrations during growth in turkeys

Abstract: The concentrations of circulating GH were low in 1-week-old birds (male plasma pool 30 ng/ml, female 32 ng/ml), reached a maximum at 7 weeks in male birds (142 +/- 26 SEM ng/ml) or 4 weeks in females (185 +/- 32 ng/ml) and then decreased to 17-3 +/- 2-8 ng/ml in males and 8-7 +/- 0-6 ng/ml in females at 17 weeks. 2. Significant inverse correlations between GH concentration and age or body weight were found (male, r = -0-693), female, r = -0-623). 3. In males, but not females, the weekly increase in body weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

1977
1977
1988
1988

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(10 citation statements)
references
References 10 publications
2
8
0
Order By: Relevance
“…The failure of GH to increase growth is consistent with the finding that the growth stimulatory potency of GH decreases as the age or body weight of birds increases (Harvey et al, 1977;Proudman and Wentworth, 1979). However, Proudman and Wentworth (1978) have demonstrated parallel dose-response curves between turkey GH and pituitary extracts, as well as among sera samples from turkeys, fowls and quail.…”
Section: Means For Body Weight Ovary-oviduct Weight Shank Length Asupporting
confidence: 82%
See 1 more Smart Citation
“…The failure of GH to increase growth is consistent with the finding that the growth stimulatory potency of GH decreases as the age or body weight of birds increases (Harvey et al, 1977;Proudman and Wentworth, 1979). However, Proudman and Wentworth (1978) have demonstrated parallel dose-response curves between turkey GH and pituitary extracts, as well as among sera samples from turkeys, fowls and quail.…”
Section: Means For Body Weight Ovary-oviduct Weight Shank Length Asupporting
confidence: 82%
“…In avian species, an inverse correlation between growth hormone (GH) and age or body weight has been found (Harvey et al, 1977;Proudman and Wentworth, 1979), and GH suppressive actions of anti-GH serum have been reported . However, a prerequisite for the onset of sexual maturity is the maturity of the gonads.…”
Section: Introductionmentioning
confidence: 98%
“…In the present investigation the variations in the concentrations of plasma GH during the growth period of control and testosterone treated turkeys were similar to those observed in previous avian studies Harvey et al, 1977a). In both groups the circulating GH level and the percentage weekly body weight gain were directly correlated, but there appears to be no simple relationship between GH concentration and growth rate, differences between the controls and implanted birds in GH level not being consistently reflected by similar differences between the groups in body weight gain.…”
Section: Resultssupporting
confidence: 90%
“…same plasma GH concentrations as birds kept in constant darkness (Harvey, 1977). However, it is possible that this fall in GH concentration might be due to the change in diet between 4 and 5 weeks of age, although in a previous study (Harvey et al, 1977a) no such fall in GH level was observed at this time in male turkeys reared under similar conditions.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation